Molecular epidemiology and antimicrobial resistance profile of ESBL-producing Escherichia Coli isolated at poultry farms and poultry meat wet-markets in Selangor, Malaysia - Bello, Aliyu Abdulrasheed (2016)
Extended spectrum β-lactamase-producing- Escherichia coli (ESBL-EC) are emerging multidrug resistant zoonotic bacteria that threaten animal production, food safety and global antimicrobial therapy. It confers resistance to first line and most widely used antibiotic in both human and veterinary chemotherapeutics. ESBL-EC is a major public health problem challenging worldwide health care facilities including Malaysia. Poultry has been suggested to serve as a major pathway for human exposure to ESBL-EC. To date, there has been little to no research on the occurrence of ESBLEC within the Malaysian poultry food chain. Hence, the objectives of the study were to determine the occurrence and distribution of ESBL-EC in broiler chickens and chicken meat, to assess their antimicrobial resistance profiles, to identify the potential risk factors associated with the occurrence of ESBL-EC, and to conduct molecular characterization and phylogenetic analysis on the ESBL-EC isolates. A cross-sectional study was conducted with 640 samples collected to determine the presence of ESBLEC from broiler poultry farms (400 samples) and wet-markets (240 samples) in Selangor, Malaysia using culture and disk combination methods and polymerase chain reaction assays. The overall study was carried out between July-2012 to February 2015. The findings demonstrated the wide distribution of ESBL-EC across the eight district areas of Selangor, Malaysia. At poultry farms, the overall proportion of ESBL-EC occurrence was 37.2%. There were significant differences in the proportions of ESBLEC that occurred among poultry farms as well as within the type of study samples. Of the eight farms, Farm A (Gombak), Farm B (Klang) and Farm C (Hulu Selangor), had the highest occurrence rate at 62%, 50%, and 50% respectively, followed by Farm D (Petaling) 38%, Farm E (Sepang) 34%, Farm F (Kuala Langat) 26% and Farm G (Kuala Selangor) 24%, and the lowest was in Farm H (Hulu Langat) 14%. Among the study samples, chicken had the highest occurrence rate at 45.4%, followed by the chicken house floor at 40%, and flies 30%, while feed and water samples were at 17.5%, and 12.5% respectively. Two hundred and forty samples (240) were collected from 40 broiler poultry stalls at wet-markets, with five stalls representing each district area. The overall prevalence was 48.8%. Among the district areas, Hulu Selangor had the highest occurrence rate at 66.7%. Moderate proportion was seen in Hulu Langat 56.7%, and Kuala Selangor 50%. The lowest proportions were found in Klang 46.7%, Sepang 46.7%, Petaling 43.3%, Gombak 40%, and Kuala Langat 40%. To determine possible factors associated with the presence of ESBL-EC at poultry farms and poultry meat wet-markets, a questionnaire was used as an instrument to obtain information and the data were analyzed using Chi-square test and logistic regression analysis at p-value of less than 0.05. At poultry farms, ten factors were found to be significantly associated in the occurrence of ESBL-EC, which were broadly classified into farm management, biosecurity, and medical history such as antibiotic usage. At the poultry meat wet-markets, only four factors had the significant association with ESBL-EC contamination, which included stall sanitation, type of counter top, source of cleaning water, and type of cutting board. The antimicrobial resistant profiles of ESBL-EC isolated from poultry farm and wetmarkets were determined using the standard disc diffusion method, according to CLSI guidelines. The ESBL-EC isolates were screened for susceptibility against 11 panels of antibiotics and 98% of the isolates showed resistance to tetracycline, 91.9% to cefotaxime, 85.2% to sulfamethoxazole/trimethoprim, 78.5% to nalidixic acid, 73.8% to chloramphenicol, 65.1% to cefpodoxime, 64.4% to ciprofloxacin, 61.1% to ceftriaxone, 59.7% to gentamicin, 53.7% to ceftazidime, and the least resistance was to aztreonam at 30.2%. At the wet-markets, ESBL-EC isolates were also tested against the same panels of 11 antibiotics and 99.1% showed resistance to tetracycline, 94.9% to cefotaxime, 93.2% to nalidixic acid, 82.1% to sulfamethoxazole/trimethoprim, 80.3% to chloramphenicol, 78.6% to ciprofloxacin, 59.8% to cefpodoxime, 41.0% to ceftriaxone, 23.9% to gentamicin, and the least resistance was to aztreonam at 21.4%. For the molecular characterization and phylogenic analysis of ESBL-EC, representative isolates from the poultry farms and wet-markets, pulsed-field gel electrophoresis (PFGE) were used. To analyse the PFGE results, 85% similarity was used as the study cut-off point. Although there is wide genomic diversity between, within and across the poultry farms and poultry meat wet- markets isolates. However, the PFGE molecular epidemiological results had evidently demonstrated genomic relationship within the selected study isolates. At the poultry farms, PFGE molecular fingerprinting revealed four major phylogroupings, with 16 isolates demonstrating genomic relationship that ranges 100% to 85% genetic similarity, between and within the poultry farms. Similarly, at the poultry meat wet-markets, four major phylogroups were detected, with 11 isolates demonstrating genomic relationship that ranges from 100% to 86% genetic similarity, between and within the poultry farms. Phylogenetic analysis for the combination of poultry farms and poultry meat wet-markets isolates revealed six major phylogroups, with eight isolates demonstrating genomic relationship across the poultry farms and poultry meat wet-markets, which range from 92% - 85% genetic similarity. In conclusion, the present study indicated the high occurrence and wide dissemination of multidrug resistant ESBL-EC at the poultry farms and wet-markets. The ESBL-EC occurrence was associated with several factors that can be broadly classified under imprudent use of antibiotics, poor husbandry, management and biosecurity practices at the farms; while the poultry meat wet-market factors included poor personal hygiene and sanitary practices, poor environmental sanitation and lack of good manufacturing practices. Thus, the findings of the study can assist to serve as a useful guide to Veterinary/Public Health authority in designing evidence-based mitigation strategies for effective control of ESBL-EC at poultry farms and poultry meat wet-markets.